Dynamic financial markets, static regulatory frameworks - James A. Haley (Centre for International Governance Innovation (CIGI), 2024)
As financial sectors around the world keep pace with rapidly changing consumer needs, creating new products, services and financial market players, regulatory frameworks are struggling to keep up due to slow-moving, legally defined entities. The tension between dynamic markets and static regulatory frameworks means that risks may emerge faster than policies can be created to mitigate them and that new firms are operating outside regulatory boundaries. This paper recommends a hybrid approach that maintains the current entities-based regulatory frameworks while promoting more consistent regulation across the financial system to address emerging systemic risks.
Keywords: 330